Prevalence of short interpregnancy interval and its associated factors among pregnant women in Debre Berhan town, Ethiopia. - Hana Mamo (Public Library of Science (PLoS), 2021)
Background Short inter-pregnancy interval is an interval of <24 months between the dates of birth of the preceding child and the conception date of the current pregnancy. Despite its direct effects on the perinatal and maternal outcomes, there is a paucity of evidence on its prevalence and determinant factors, particularly in Ethiopia. Therefore, this study assessed the prevalence and associated factors of short inter-pregnancy interval among pregnant women in Debre Berhan town, Northern Ethiopia. Methods A community based cross-sectional study was conducted among a randomly selected 496 pregnant women in Debre Berhan town from February 9 to March 9, 2020. The data were collected by using an interviewer-administered questionnaire and analyzed using STATA (14.2) statistical software. To identify the predictors of short inter-pregnancy interval, multivariable binary logistic regression was fitted and findings are presented using adjusted odds ratio (AOR) with 95% confidence interval (CI). Result The overall prevalence of short inter-pregnancy interval (<24 months) among pregnant women was 205 (40.9%). Being over 30 years of age at first birth (AOR = 3.50; 95% CI: 2.12-6.01), non-use of modern contraceptive (AOR = 2.51; 95% CI: 1.23-3.71), duration of breastfeeding for less than 12 months (AOR = 2.62; 95% CI: 1.32-5.23), parity above four (AOR = 0.31; 95% CI: 0.05-0.81), and unintended pregnancy (AOR = 5.42; 95% CI: 3.34-9.22) were independently associated factors with short inter-pregnancy interval. Conclusion Despite the public health interventions being tried in the country, the prevalence of short inter-pregnancy interval in this study is high. Therefore, it implies that increasing contraceptive use and encouraging optimal breastfeeding might help in the efforts made to avert the problem.